C reactive protein impairs adaptive immunity in immune cells of patients with melanoma. Issue 1 (16th April 2020) - Yoshida, Tatsuya; Ichikawa, Junya; Giuroiu, Iulia; Laino, Andressa S; Hao, Yuhan; Krogsgaard, Michelle; Vassallo, Melinda; Woods, David M; Stephen Hodi, F; Weber, Jeffrey
Abstract : Background: High C reactive protein (CRP) levels have been reported to be associated with a poor clinical outcome in a number of malignancies and with programmed cell death protein 1 immune checkpoint blockade in patients with advanced cancer. Little is known about the direct effects of CRP on adaptive immunity in cancer. Therefore, we investigated how CRP impacted the function of T cells and dendritic cells (DCs) from patients with melanoma. Methods: The effects of CRP on proliferation, function, gene expression and phenotype of patient T cells and DCs, and expansion of MART-1 antigen-specific T cells were analyzed by multicolor flow cytometry and RNA-seq. Additionally, serum CRP levels at baseline from patients with metastatic melanoma treated on the Checkmate-064 clinical trial were assessed by a Luminex assay. Results: In vitro, CRP inhibited proliferation, activation-associated phenotypes and the effector function of activated CD4+ and CD8+ T cells from patients with melanoma. CRP-treated T cells expressed high levels of interleukin-1β, which is known to enhance CRP production from the liver. CRP also suppressed formation of the immune synapse and inhibited early events in T-cell receptor engagement. In addition, CRP downregulated the expression of costimulatory molecules on mature DCs and suppressed expansion of MART-1-specific CD8+ T cells in a dose-dependent manner by impacting on both T cells and antigen-presenting cells. High-serum CRP levels at baseline were significantly associated with a shorter survival in both nivolumab-treated and ipilimumab-treated patients. Conclusions: These findings suggest that high levels of CRP induce an immunosuppressive milieu in melanoma and support the blockade of CRP as a therapeutic strategy to enhance immune checkpoint therapies in cancer. Trial registration number: NCT01783938 and NCT02983006 .